SERPIND1 Affects the Malignant Biological Behavior of Epithelial Ovarian Cancer via the PI3K/AKT Pathway: A Mechanistic Study - Guo, Qian; Zhu, Liancheng; Wang, Caixia; Wang, Shuang; Nie, Xin; Liu, Juanjuan; Liu, Qing; Hao, Yingying; Li, Xiao; Lin, Bei (Frontiers in Oncology, 2019)
Serpin family D member 1 (SERPIND1) belongs to the serine protease inhibitor family. Its role in cancers has gradually attracted interest from researchers in recent years. However, the role of SERPIND1 in the development of epithelial ovarian cancer remains poorly understood. This study aimed to investigate the expression and clinical significance of SERPIND1 in epithelial ovarian cancer, as well as its effect on the malignant biological behavior of ovarian cancer cells and the related regulatory mechanisms. We found that SERPIND1 expression was significantly elevated in epithelial ovarian cancer. Patients with higher expression of SERPIND1 in ovarian cancer tissues had poor prognoses. SERPIND1 promoted the proliferation, migration, invasion, G1-to-S phase transition, and epithelial–mesenchymal transition of ovarian cancer cells and inhibited their apoptosis by promoting phosphorylation in the phosphoinositide 3-kinase/protein kinase B (PI3K/AKT) pathway. Meanwhile, the inhibition of SERPIND1 expression in ovarian cancer cells resulted in opposite effects. The addition of the PI3K/AKT pathway inhibitor LY294002 to SERPIND1- overexpressing cells could reverse the promoting effect of SERPIND1 on the malignant biological behavior of ovarian cancer cells. Further, nuclear factor kappa B subunit 1, a transcription factor, could bind to the promoter region of SERPIND1 and regulate SERPIND1 expression. In conclusion, our results indicated that SERPIND1 could be an effective marker for assessing the prognosis of ovarian cancer. By elucidating the mechanism underlying the promotion of malignant biological behavior of ovarian cancer by SERPIND1, we demonstrated that SERPIND1 could potentially serve as a novel drug target.